Patterns of Teaching-Learning Interaction in the EFL Classroom - Fatimah Mulya Sari (Universitas Teknokrat Indonesia, 2018)
The successfullness of teaching-learning process is highly influenced by the patterns of interactions appeared in the classroom activities. Through this case study, the purpose of this paper is to explore the patterns of interaction during teaching and learning proccess. Two accellerated classes were observed and recorded to gain the data. The findings revealed that the patterns of interaction emerged in the first class were group work, choral responses, closed-ended teacher questioning (IRF), individual work, student initiates-teacher answers, open-ended teacher questioning, and collaboration. Meanwhile, the patterns of interaction in the second class showed closed-ended teacher questioning (IRF), open-ended teacher questioning, choral responses, student initiates-teacher answers, group work, and individual work pattern. The patterns of interaction were produced from teacher and student(s) and/or student(s) and student(s) in relation to the teacher talk and the students talk categories used during learning activities. These patterns were produced constantly. They are to show that the teaching-learning process was not always dominated by the teacher. Most students actively participate as well in any classroom activity. Thus, these patterns absolutely increase the students talk and students’ participation in the class. It is necessary for teachers to reorganize the active activities which might foster more interaction in the classroom.Key Words: EFL Classroom, patterns of interaction, teaching-learning process.